An investigation into the impact of an indicated CBT-based intervention on anxiety in secondary school students. - Lake, Daniel J. (2014)
This study presents a mixed methods investigation into the efficacy of an indicated CBT-based intervention for addressing anxiety in a sample of secondary school students within the UK.